PENERAPAN MODEL PEMBELAJARAN COOPERATIVE COURSE REVIEW HORAY UNTUK MENINGKATKAN MOTIVASI BELAJAR DI SMP NEGERI 4 TAKALAR - Nurhikmah; Subaedah; Ahmad; Akil, M; Nengsih, Ratika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of the Cooperative Course Review Horay (CRH) learning model in improving students' learning motivation in the subject of Islamic Religious Education in class VIII A of SMP Negeri 4 Takalar. This research is motivated by the low learning motivation of students which is characterized by a lack of activeness, participation, and enthusiasm in following the learning process because it is still dominated by the lecture method. The type of research used is Classroom Action Research (CAR) with the Suharsimi Arikunto model which consists of four stages, namely planning, implementation, observation, and reflection. The study was conducted in two cycles with 29 research subjects of class VIII A of SMP Negeri 4 Takalar. Data collection techniques include observation, interviews, questionnaires, and documentation, while data analysis is carried out descriptively quantitatively and qualitatively. The results of the study indicate that the application of the Cooperative Course Review Horay (CRH) learning model is able to improve students' learning motivation. In the pre-cycle, students' learning motivation is still relatively low and has not met the success indicators. After the implementation of the CRH model in cycle I, learning motivation began to increase, although there were still some students who were less active in discussions and were not confident in expressing their opinions. Improved actions in cycle II provided more optimal results. Students became more active, enthusiastic, confident, and able to work together in groups during the learning process. The results of the questionnaire showed that the average learning motivation reached 90.07 with the majority of students in the very good and good categories. Thus, it can be concluded that the implementation of the Cooperative Course Review Horay (CRH) learning model is effective in increasing student learning motivation in the subject of Islamic Religious Education in class VIII A of SMP Negeri 4 Takalar.